Entropy squeezing for qubit-field system in the presence multi-photon process under decoherence effect - Sayed, Abdel-Khalek; Khalid, Berrada; Abdel Shafy Fahmy, Obada; Wahiddin, Mohamed Ridza (Springer, 2015)
In this paper, we study in detail the dynamics of field entropy squeezing (FES)for qubit-field system whose dynamics is described quantitatively in terms of multi-photon and phase damping processes. Especially, considering a two-level atom interacts with a single-mode quantized field in a coherent state inside a phase-damped cavity, and taking into account the number of multi-photon transitions and phase damping effect. The FES is investigated during the time evolution as a function of involved parameters in the system. This quantity exhibits a richer structure to provide different phenomena by proper choice of the involved system parameters. Our results show that the initial coherent field type, number of photons transition and decoherence parameter play a crucial role on the evolution of FES during the time evolution under decoherence effect. An interesting monotonic relation between FES, Wehrl entropy and negativity is observed during the time evolution.